2013
DOI: 10.1007/s13105-013-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products and diabetic nephropathy: a comparative study using diabetic and normal rats with methylglyoxal-induced glycation

Abstract: Hyperglycemia-related advanced glycation end product (AGE) formation is a key mechanism in diabetic nephropathy. Since methylglyoxal (MG) is a potent AGE precursor, we aimed to assess the role of MG-related AGE formation in the progression of renal damages. A comparative study between Wistar (W, normal) and Goto-Kakizaki (GK, nonobese type 2 diabetic) rats was performed at 6 and 14 months old and after 14 weeks of MG administration to 6-month-old rats. Diabetic rats showed progressive structural, biochemical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Consistent with in vitro data, alterations of podocyte adhesion to the basal membrane were observed in diabetic rats, due to the loss of integrin function, as well as tubulointerstitial fibrosis . Our group has recently compared the effects of dietary MG supplementation with diabetic rats and observed similar glomerular effects of MG with the endogenous lesions of diabetic rats . Accordingly, decreased kidney GLO1 expression and increased MG formation during ischemia–reperfusion were observed to result in tubulointerstitial lesions.…”
Section: Pathophysiological Relevance Of Methylglyoxal In Metabolic Dsupporting
confidence: 81%
“…Consistent with in vitro data, alterations of podocyte adhesion to the basal membrane were observed in diabetic rats, due to the loss of integrin function, as well as tubulointerstitial fibrosis . Our group has recently compared the effects of dietary MG supplementation with diabetic rats and observed similar glomerular effects of MG with the endogenous lesions of diabetic rats . Accordingly, decreased kidney GLO1 expression and increased MG formation during ischemia–reperfusion were observed to result in tubulointerstitial lesions.…”
Section: Pathophysiological Relevance Of Methylglyoxal In Metabolic Dsupporting
confidence: 81%
“…In vivo, it has recently been demonstrated that long-term MGO administration (14 weeks) to normal rats leads to structural changes in the adipose tissue microvasculature, hypoadiponectinaemia and lipolysis. These effects are associated with increased tissue glycation and impaired expression of apoptotic and angiogenic markers, but not with insulin resistance [174,175]. In contrast, shortterm MGO administration (8 weeks) causes much less severe effects, despite the fact that tissue accumulation of CEL takes place [176,177].…”
Section: Obesitymentioning
confidence: 99%
“…Glyoxal is a product of cellular peroxidation and protein glycation. Advanced glycation endproducts (AGEs) are associated with the progression of diabetic nephropathy and increased pro-inflammatory cytokines such as IL-1β, which can both be ameliorated by methylglyoxal trapping [16, 17, 18, 19]. Also, diabetics tend to excrete more oxalate than healthy individuals [20, 21, 22].…”
Section: Oxalate – Endogenous Productionmentioning
confidence: 99%